IDENTIFICATION OF COLD AND HEAT-INDUCED DIFFERENTIALLY EXPRESSED GENES IN ALFALFA (MEDICAGO SATIVA L.) LEAVES - Ki-Won Lee; Md. Atikur Rahman; Gi Jun Choi; Ki-Yong Kim; Hee Chung Ji; Jong Geun Kim; Sang-Hoon Lee (Journal of Animal and Plant Sciences, 2017)
Alfalfa is an important forage legume cultivated as livestock feed crop with high yield potential. The productivity of alfalfa is reduced by multiple abiotic stresses. In this study, we identified cold and heat induced differentially expressed genes (DEGs) in alfalfa leaves using annealing controlled primer-based (ACP) approach. Three-week-old alfalfa seedlings were exposed to cold (4oC for 6 h) and heat (42oC for 6 h) treatments, respectively. Control plants were maintained at normal temperature (25oC). In this molecular technique, over 100 ACPs sets were applied for this investigation. Total 10 differentially expressed genes (DEGs) were obtained during cold or heat stresses. Out of 10 DEG, 7 (3 were cold and heat, 3 were cold, and 1 heat induced) were up-regulated response to either cold and/or heat stress. Sequencing was performed for the functional analyses of these stress induced DEGs. The identified DEGs were corresponding as ribosomal protein L20, S-adenosylmethionine decarboxylase, Cold-acclimation specific protein 30, DNAJ-like protein, and Heat shock 22 kDa protein. These genes were mostly involved in stress tolerance in plants. These stress-induced genes would be useful candidates for stress tolerant crop production.
Keywords: Alfalfa; DEGs; Tolerance; Cold stress; Heat stress